Teachers and Students' Perception Towards the Textbook: “New Generation English" - Lamichhane, Bina (New Journey, 2024)
This research article entitled, Teachers and Students' Perception Towards the Textbook: “New Generation English" attempts to analyse the textbook "New Generation English" which was designed and edited by E.L.T experts of the department of English Education T.U. namely Awasthi, J.R. Bhattarai, G.R, and Khaniya T.R. This English textbook has been introduced for the students of three year Bachelor's degree in education (B.Ed) to meet the needs of Nepalese learners of English. It is an integrated course aimed at developing general proficiency in the English language with special emphasis on developing reading and writing skills. The objectives of this research study are to examine the quality of the poems in terms of their physical and linguistic features and to analyze the poems included in “New Generation English” in terms of language and their appropriateness for the target groups . Questionnaires and interviews were the major tools used to collect the necessary data. The sample population consisted of 10 subject teachers who have been experienced for at least a year and forty students who are studying B.Ed second year from different campuses affiliated to T.U. Regarding theorganization of text and exercises and texts, 75 % of students were found satisfied and 25 % of students were found dissatisfied. Regarding the relevancy of the texts, Out of the 10 teachers 6 agreed 2 disagreed and 2 remained neutral. It was found that 60 % of the teachers and 65 % of the students agreed on the topic.